Design of Bionic Knee Joint Mechanism based on Tensegrity Structure - Wei Zhang; Lin Liu; Guangsheng Song (Jixie chuandong)
On the basis of the locomotion mechanism and biological characteristic of the human knee joint，a structural mapping model of bionic knee joint mechanism is established through equivalent mapping and bionic design method which is based on a C4S2 plane tensegrity structure. By using the mechanism configuration analysis method，the stability of the mechanism is verified. The inverse dynamics method is used to match the spring stiffness and solve the kinematics through the rigid-flexible coupling characteristics of the human knee joint. The mechanism is simulated by Adams. The bionic knee joint mechanism can realize the motion range of human-like knee joint movement by the simulation results. Compared with the simulation results and the theoretical calculation results，the simulation results and the test results，the validity and feasibility of the proposed theory and design of the bionic knee joint mechanism are verified. The bioinspired knee mechanism based on tensegrity structure which is realized the flexibility，semi-automatic recovery and self-locking meet the requirements of bionic design.